NONINVASIVE METHOD FOR MAPPING BURIED COAL ASH (World Science, 2025)
Coal Combustion Products (CCP) are one of the largest industrial waste streams in the world and, in some cases, the final disposition of this toxic material is not carefully controlled resulting in undocumented landfills, illegal dump sites, and mixing with Municipal Solid Waste (MSW). A new approach for discovering and mapping CCP sites based on radiation measurements has been tested in a historicaly inducstrial on the east coast of the United States where CCP was extensively used as fill material.